Evaluation of Certain Insecticides Against Sesame Leaf Webber and Capsule Borer (Antigastra catalaunalis Duponchel) - Omprakash, S.; Reddy, C. Narendra; Sree, M. Swarna; Babu, T. Kiran; Sreedhar, M. (International Journal of Bio-resource and Stress Management, 2022)
A field experiment trial was conducted during (summer) 2019 and 2020 to evaluate the efficacy of certain insecticides against Antigastra catalaunalis on sesame. A total of seven selected insecticide molecules viz., acephate 75% SP, spinosad 45% SC, profenophos 50% EC, imidacloprid 17.8% SL, ethofenprox 10% EC, chlorantraniliprole 18.5% SC and azadirachtin 1500 ppm were tested for their efficacy. Among selected insecticides, chlorantraniliprole 18.5% SC @ 0.3 ml l-1 (90.28%) was found to be the most effective in reduction of A. catalaunalis larval population followed by spinosad 45% SC @ 0.3 ml l-1 with 80.23 % larval reduction over control. The next best treatments were profenophos 50% EC @ 2.0 ml l-1, acephate 75% SP @ 1.0 g l-1, ethofenprox 10% EC @ 2.0 ml l-1 and imidacloprid 17.8% SL @ 0.4 ml l-1 recorded 73.48%, 62.91%, 58.77% and 53.45% mean reduction of A. catalaunalis larval population, respectively. The azadirachtin 1500 ppm @ 5.0 ml l-1 (29.88%) recorded lowest reduction of A. catalaunalis larval population compared to untreated control. The highest seed yield of 801 kg ha-1 was recorded in chlorantraniliprole 18.5% SC @ 0.3 ml l-1 treatment followed by spinosad 45% SC @ 0.3 ml l-1 (783 kg ha-1) ) and the least seed yield was obtained in azadirachtin 1500 ppm @ 5.0 ml l-1 treatment (550 kg ha-1). The highest incremental cost benefit ratio was recorded in profenophos treatment (1:3.22) followed by chlorantraniliprole treatment (1:3.12) and spinosad (1:2.96) treatment.